Core clock gene Bmal1 deprivation impairs steroidogenesis in mice luteinized follicle cells. Issue 6 (December 2020) - Wang, Yizi; Chen, Minghui; Xu, Jian; Liu, Xinyan; Duan, Yuwei; Zhou, Canquan; Xu, Yanwen
Abstract : Luteinization is the event of corpus luteum formation, a way of follicle cells transformation and a process of steroidogenesis alteration. As the core clock gene, Bmal1 was involved in the regulation of ovulation process and luteal function afterwards. Till now, the underlying roles of luteinization played by Bmal1 remain unknown. To explore the unique role of Bmal1 in luteal steroidogenesis and its underlying pathway, we investigated the luteal hormone synthesis profile in Bmal1 knockout female mice. We found that luteal hormone synthesis was notably impaired, and phosphorylation of PI3K/NfκB pathway was significantly activated. Then, the results were verified in in vitro cultured cells, including isolated Bmal1 interference granulosa cells (GCs) and theca cells (TCs), respectively. Hormones levels of supernatant culture media and mRNA expressions of steroidogenesis-associated genes ( star, Hsd3β2, cyp19a1 in GCs, Lhcgr, star, Hsd3β2, cyp17a1 in TCs) were mutually decreased, while the phosphorylation of PI3K/NfκB was promoted during in vitro luteinization. After PI3K specific-inhibitor LY294002 intervention, mRNA expressions of Lhcgr and Hsd3β2 were partially rescued in Bmal1 interference TCs, together with significantly increased androstenedione and T synthesis. Further exploration in TCs demonstrated BMAL1 interacted directly but negatively with NfκB p65 (RelA), a subunit which was supposed as a mediator in Bmal1 -governed PI3K signaling regulation. Taken together, we verified the novel role of Bmal1 in luteal steroidogenesis, achieving by negative interplay with RelA-mediated PI3K/NfκB pathway.